Hierarchical Clustering on the Torus - Ashis SenGupta; Moumita Roy (Journal of the Indian Society of Agricultural Statistics, 2026)
The aim of this paper is to introduce hierarchical clustering for bivariate circular or toroidal data. Here a mixture model approach is used as for model based clustering. Here, the clustering is performed in two stages, the first stage being based on the marginal distribution of one of the circular variables and the second stage being based on the conditional distribution of the other variable given the former. In particular, two types of such mixture models are constructed. A real life application on gene data is made to illustrate the use of the proposed approach. Comparison of the two models is also done based on this example.